Planning for Raw Material Inventory Needs at PT. X Semarang With Min-Max Method - Jihan Pradesi; Hendrik Cahya Prabowo (Institut Teknologi Bisnis AAS Indonesia, 2021)
The main goal of each company is to optimize the company's profit because it will have an impact on business continuity and the most important element in achieving this goal is the existence of inventory in the form of goods. Then a good company is a company that has a good and neat system in terms of collecting data on the production of goods and their inventory. This study aims to determine the inventory of goods available in Company X and improve the data input system at the company.